The Pathophysiology of Disseminated Intravascular Coagulation - ten Cate, Hugo; Timmerman, Janneke J.; Levi, Marcel (Thrombosis and Haemostasis, 1999)
Disseminated intravascular coagulation (DIC) can be defined as “an acquired syndrome characterized by the activation of intravascular coagulation up to intravascular fibrin formation. The process may be accompanied by secondary fibrinolysis or inhibited fibrinolysis.”1 Being an acquired disorder, DIC occurs in a wide range of underlying disease states, including sepsis (both by Gram positive and Gram negative bacteria), burns, preeclampsia, malignancy, and polytrauma.1 In the majority of conditions, the pathogenesis of DIC remains only partly understood, an exception is Gram negative septicemia. In the following chapter, we will discuss the presumed mechanism by which DIC is elicited in different pathological states. The initiation of DIC follows the presentation of the glycoprotein tissue factor (TF) at a cellular surface, being either an intact or perturbed cell, or a cell membrane remnant.2 The extracellular TF molecules may interact with circulating factor VIIa to form a catalytic complex. The complex binds the coagulation zymogen factors IX and X. This leads to proteolytic cleavage of these molecules, yielding enzymatically active factors IXa and Xa and promoting the activation of prothrombin to thrombin (Fig. 1).